Design of Coaxial Differential Planetary Mechanism Reducer - Song Qihui; Qi Keqiang; Kong Fankun (Jixie chuandong)
In order to study the gear transmission principle of differential planetary mechanism of reducer,the teeth-distributing calculating and the transmission ratio confirming of the differential mechanism are carried out.According to the analysis and calculation results,the overall structure design of reducer is carried out.The results show that,the designed structure can meet the design requirements of coaxial,inversion,constant output.